ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN PROBOLINGGO - Zulfia Hasanah Eka Putri; Galih Wicaksono (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
Land and Building Tax in the Probolinggo Regency area is an important source of local revenue to finance the implementation of development. This study aims to determine the level of effectiveness of the Rural and Urban Land and Building Tax (PBB P2) Probolinggo Regency, and to determine the level of Rural and Urban Land and Building Tax contribution to Regional Original Income (PAD) in Probolinggo Regency in 2018-2020. . In this study using qualitative methods and descriptive approaches. For the type of data used in the study, namely using the type of secondary data obtained from BPS Probolinggo Regency. The results of the research show that the level of effectiveness of PBB P2 in 2018-2020 each year is still less effective, while the level of contribution of PBB P2 to PAD shows that in 2018-2020 the level of contribution is in the very poor category